The Effect of Red Dragon Fruit Peel Flour (Hilocereus polyhrizus) In Feed on Improving the Color of Koi Betta Fish - Darna Susantie; Muhammad Fiqih Zulendra (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
Dragon fruit skin contains betacyanin, a pigment responsible for the red color. Red dragon fruit skin can be used as a flour ingredient in artificial feed containing carotenoids, which is useful for enhancing the color of ornamental fish. The aim of this research is to determine the effect of using red dragon fruit peel flour concentration in feed on improving the color of koi betta fish. The research implementation period was 55 days from October 6 to November 27, 2025, including 1 week pre-research, 3 days without test feed and 45 days of research. The test fish used in the study were 12 koi betta fish, with four treatments and three replications. The test material used was red dragon fruit peel powder added to the betta feed. The addition of red dragon fruit peel flour in feed for koi betta fish shows an increase in the brightness of different colors, this is due to the different doses given in the feed. The highest color enhancement was achieved at doses of 20% and 30%. Adding red dragon fruit peel powder to the feed is well absorbed by the fish, resulting in an increase in the brightness of the koi betta's color. The survival rate of koi betta fish for 45 days for all treatments was 100%.